Prevalence and determinants of exclusive breastfeeding in the city of Serrana, São Paulo, Brazil - Queluz, Mariângela Carletti; Pereira, Maria José Bistafa; Santos, Claudia Benedita dos; Leite, Adriana Moraes; Ricco, Rubens Garcia (Revista da Escola de Enfermagem da USP, 2012)
The objective of this cross-sectional and quantitative study was to identify the prevalence and determinants of exclusive breastfeeding among infants less than six months of age in the city of Serrana, Sao Paulo, Brazil in 2009. A validated semi-structured questionnaire was administered to the guardians of the children less than six months of age who attended the second phase of a Brazilian vaccination campaign against polio. Univariate and multivariate analysis presented in odds ratios and confidence intervals was accomplished. Of the total of 275 infant participants, only 29.8% were exclusively breastfed. Univariate analysis revealed that mothers who work outside the home without maternity leave, mothers who did not work outside the home, adolescent mothers, and the use of pacifiers have a greater chance of interrupting exclusive breastfeeding. In the multivariate analysis, mothers who work outside the home without maternity leave are three times more likely to wean their children early. Results provide suggestions for the redirection and planning of interventions targeting breastfeeding.